2015
DOI: 10.1063/1.4905194
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural properties of plasma-treated Cordyceps bassiana spores as studied by circular dichroism, absorption, and fluorescence spectroscopy

Abstract: To understand the killing mechanism of fungal spores by plasma treatment, the optical, structural, and biological properties of the insect pathogenic fungus Cordyceps bassiana spores were studied. A nonthermal atmospheric-pressure plasma jet (APPJ) was used to treat the spores in aqueous solution. Optical emission spectra of the APPJ acquired in air indicated emission peaks corresponding to hydroxyl radicals and atomic oxygen. When the APPJ entered the aqueous solution, additional reactive species were derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 72 publications
1
27
0
Order By: Relevance
“…Spores that survived could germinate and grow as mycelia. This decreasing spore viability with increasing plasma treatment time agrees with previous results regarding APPJ treatment of C. bassiana and C. pruinosa spores [12,13]. Although the viability of C. pruinosa spores treated by the soft plasma jet is similar to that treated by the APPJ, there are important differences between this research and the previous study [13].…”
Section: Electrophoresis Of Fungal Spore Dnasupporting
confidence: 89%
See 2 more Smart Citations
“…Spores that survived could germinate and grow as mycelia. This decreasing spore viability with increasing plasma treatment time agrees with previous results regarding APPJ treatment of C. bassiana and C. pruinosa spores [12,13]. Although the viability of C. pruinosa spores treated by the soft plasma jet is similar to that treated by the APPJ, there are important differences between this research and the previous study [13].…”
Section: Electrophoresis Of Fungal Spore Dnasupporting
confidence: 89%
“…When the soft plasma jet was introduced into the aqueous solution, additional reactive species could be induced from the interaction between plasma radicals and water molecules [4,12]. Among the reactive oxygen species derived from the interaction of plasma radicals with the aqueous solution, H 2 O 2 has the highest stability and the lowest reactivity [21].…”
Section: Plasma-activated Water and Plasma-induced Intracellular Rosmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been partially confirmed through circular dichroism (CD) and fluorescence studies of fungal spores where the spectral peak corresponding to cell wall protein was found to decay after plasma treatment. It has also been observed that plasma treatment results in destruction of the DNA in fungal spore, which has been confirmed from the decaying CD spectrum signature, and loss of band intensity after gel electrophoresis (Lee et al., ). It is worthwhile noting that the extent of changes in fungal spores is a function of the level of exposure to plasma species.…”
Section: Mechanism Of Action Of Plasma Against Fungimentioning
confidence: 75%
“…These changes became prominent only after 60 s treatment, and after 180 s the cells were flattened. Lee et al (2015) observed through scanning electron microscopy (SEM) that plasma treatment (using an atmospheric jet) resulted in considerable morphological alterations in fungal spores of Cordyceps bassiana, causing rupture, flattening and shrinkage, with surface wrinkling. SEM observation of Dasan, Boyaci, and Mutlu (2017) have also revealed that the spores of A. parasiticus lose their integrity after plasma treatment (for 30 s using a fluidized plasma bed) and the cell contents disperse into clusters.…”
Section: Mechanism Of Action Of Plasma Against Fungimentioning
confidence: 99%